2019
DOI: 10.4049/jimmunol.1801585
|View full text |Cite
|
Sign up to set email alerts
|

The Lysophosphatidylcholine Transporter MFSD2A Is Essential for CD8+ Memory T Cell Maintenance and Secondary Response to Infection

Abstract: Access to nutrients is critical for an effective T cell immune response to infection. Although transporters for sugars and amino acids have previously been described in the context of the CD8 + T cell immune response, the active transport of exogenous fatty acids has remained enigmatic. In this study, we discovered that the sodium-dependent lysophosphatidylcholine (LPC) transporter major facilitator superfamily domain containing 2A (MFSD2A) is upregulated on activated CD8 + T cells and is required for memory T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…To this end, prior studies have shown that the lysophosphatidylcholine (LPC)-scavenging receptor MFSD2A is highly expressed in activated T cells and memory T cells, and transient increases in intra-cellular LPCs parallels and potentiates T cell activation. 32 , 39 , 40 Conditional loss of MFSD2A in CD8 + T cells was shown to reduce LPC uptake, resulting in attenuated effector function and reduced memory T cell formation and maintenance. 39 Therefore, it is likely that lower bioavailability of circulating lysophospholipids may diminish proliferation and functions of CAR-T cells, resulting in lower clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, prior studies have shown that the lysophosphatidylcholine (LPC)-scavenging receptor MFSD2A is highly expressed in activated T cells and memory T cells, and transient increases in intra-cellular LPCs parallels and potentiates T cell activation. 32 , 39 , 40 Conditional loss of MFSD2A in CD8 + T cells was shown to reduce LPC uptake, resulting in attenuated effector function and reduced memory T cell formation and maintenance. 39 Therefore, it is likely that lower bioavailability of circulating lysophospholipids may diminish proliferation and functions of CAR-T cells, resulting in lower clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Piccirillo et al have reported that MFSD2a is expressed in T cells, being its expression essential for the correct functionality of CD8+ T Lymphocytes. These authors have observed that the expression of MFSD2a early during the CD8+ effector T cell immune response has critical long-term effects, as this transporter is required for the uptake of LPC into activated T cells, which is essential for the maintenance and turnover of memory CD8+ T cells (46). In this regard, a limitation of our study is that, although we have been able to analyze the expression of MFSD2a in whole maternal blood, we were not able to determine by flow cytometry or microscopy which populations of cells were actually those expressing this protein, and if the cellular profile expression of MFSD2a would be different in GDM patients and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…To specifically determine the function of Mfsd2a in AT2 cells in the lung, we generated an inducible AT2-specific Mfsd2a deletion model using Sftpc-CreER T2 (Mfsd2a fl/fl Sftpc-CreER T2 , henceforth designated AT2aKO). We chose to focus on the study of an AT2 specific model rather than whole body Mfsd2a knockout mice because the latter model presents with multiple phenotypes that could confound our studies such as increased plasma levels of LPCs, markedly small size, and increased basal metabolic rate, and altered T cell immune function [33,34]. Immunohistochemical staining for endogenous Mfsd2a confirmed localization of Mfsd2a to AT2 cells of the lungs of 2a fl/fl controls and indicated that Mfsd2a was successfully deleted from AT2 cells in AT2aKO mice as early as 10 days following tamoxifen administration (Fig.…”
Section: Mfsd2a Is Expressed In Lung At2 Cellsmentioning
confidence: 99%
“…Although Mfsd2a preferentially transports LPC containing polyunsaturated fatty acid (PUFA) moieties, it also transports saturated LPCs like LPC-palmitate [22,32]. Importantly, Mfsd2a expression is not confined to the brain or eye vasculature but also found to be expressed in other cell types and tissues such as liver, intestine and lymphocytes [33,34].…”
Section: Introductionmentioning
confidence: 99%